Survey of MAC Protocol for Wireless Sensor Networks - Verma, Akansha; Singh, M. P.; Singh, Jyoti Prakash; Kumar, Prabhat (2015 Second International Conference on Advances in Computing and Communication Engineering, 2015)
Energy being a key constraint in wireless sensor networks (WSN) became a significant area of interest for various researches in WSN. A lot of work on energy conservation at different layers of protocol stack is present till date, of which energy conservation at Medium access control (MAC) layer is catching a lot of attention. Researchers have proposed several protocols for energy conservation in WSN at MAC layer. This paper presents a survey on some of the popular MAC layer protocols. It also provides a brief analysis of these protocols which could be helpful in future work in this direction. This paper also provides a reference for further research in this area giving an insight on energy conservation at MAC layer.